Life Skills Acquired Through Swimming Context in Relation to Students' Academic Achievement - Samira Orabi; Manal Bayyat; Mohammad H. Abu Altaieb (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
This study aims to investigate the relation between life skills acquired through swimming context and students' academic achievement. The population of this study were students who attended one of the three levels of the swimming courses in the School of Physical Education /University of Jordan (n= 259). The study sample consisted of 211 students distributed into basic, intermediate, and advanced swimming courses (N=109, 73, 29, respectively). "Life skills through swimming context scale" was used to collect the life skills required data, in addition to the students' academic achievement throughout the different swimming courses. Percentages, means and standard deviation were used to describe the collected data. Results of the study show that the sample of the study had acquired life skills through swimming context on a high-level scale. Taking responsibility was the most important life skill learned through the swimming context (88%), followed by communication and self-confidence/ self-esteem (86%), teamwork (85%) and finally problem-solving (80%). Furthermore, significant differences occurred in students' academic achievement according to the swimming course level in favor of the advanced level students. We found a significant relation between acquired life skills and the students' academic achievement of all group sample. In conclusion, students' academic achievement level positively reflected the life skills they acquired through the swimming context. Life skills can play an important role in the promotion of mental well-being as well as academic achievement. Therefore, it is important to design comprehensive life skill-based study plans in different sport fields to enhance students' life skills through sports.